Impacto de la regulación en la eficiencia asignativa del mercado spot eléctrico colombiano (2015)
This paper uses an ARCH regression model to analyze the effect of several regulatory measures and fundamental factors (the relationship between commercial demand and real availability, El Niño, and water supplies) on the spot price in the Colombian wholesale power market. The results indicate that the regulations established by the Electricity and Gas Regulatory Commission have had a substantial and statistically-significant effect on spot prices. In addition, El Niño and hydro supplies have a positive and negative respectively effect on the spot price, due to the large share of hydropower in this market.